One Concept, Multiple Realizations A Case Study on Notation in Compositional Practice: Dark Bright - Amy T. Salsgıver (Konservatoryum)
This paper explores how diverse modes of notation, grounded in a single germinal idea, can yield multiple, distinct musical outcomes. Through a practice-based ap proach, the study investigates how different iterations of a musical work can emerge by employing, suppressing, or accentuating compositional, improvisational, and tran scriptional techniques. Rather than focusing on fixed forms, the study highlights the creation of musical atmospheres, spaces for exploration, and sound-based interaction, promoting a post-colonial approach to musical scores and notation that moves beyond Eurogenetic traditions. This approach encourages collective authorship and empathy within the process of musical generation. Each work employs a different approach to the communication of musical ideas to performers, with the choice of notational or scoring modality tailored to the specific circumstances of each piece. The resulting compositions, and conclusions based on comparing their outcomes, underscores the f luidity between composer and performer roles, reflecting on how shifting creative ownership can lead to more collaborative and transcultural music-making, while still allowing for a recognizable cohesion connecting the composition to its composer.